Characterization and comparation of toxicity between natural realgar and artificially optimized realgar - Luo, Lu; Xin, Xueying; Wang, Qiaochu; Wei, Mengjia; Huang, Nanxi; Gao, Shuangrong; Gu, Xuezhu; Li, Raorao (Frontiers in Pharmacology, 2024)
Objective: Realgar possesses important medical properties. This article aims to evaluate realgar and emerging artificially optimized realgar to ensure safe clinical use.Methods: Multiple techniques were employed to test natural realgar and artificially optimized realgar. Soluble arsenic content in representative samples were measured.Natural realgar and artificially optimized realgar were administered to KM mice via gavage for 28 days, and the extent of liver and kidney tissue damage, arsenic accumulation and form of arsenic were measured.Results: Natural realgar and artificially optimized realgar can be distinguished by their physical properties or spectral signatures. ICP-MS and EPMA identified different contents of elements between two groups. In simulated gastric and intestinal fluids, only As(III) and As(V) were detected. Toxicity experiments in vivo demonstrate that both groups caused minimal liver and kidney damage at a dose of 30 mg•kg -1 . At a dose of 180 mg•kg -1 , artificially optimized realgar caused significantly greater liver and kidney damage.The differences between natural realgar and artificially optimized realgar were successfully distinguished through several methods. In vitro experiments showed that As is the main component exerting their medicinal effects. In vivo toxicity tests demonstrated that at higher dose, artificially optimized realgar exhibited significantly